Finite Element Analysis of All Composite CNG Cylinders. (2015) - Nirbhay, Mayank; Juneja, Sagar; Dixit, Anurag; Misra, R.K.; Sharma, Satpal
Abstract: It is the need of time to ensure the safe operation of compressed natural gas (CNG) cylinders under adverse conditions; the extremities should be predicted under which these cylinders continue to operate without failing. A comprehensive modelling approach in order to predict the behavior and failure of CNG cylinders under various loading conditions has been proposed using Finite Element (FE) Software-ANSYS. In the present investigation two different materials viz. glass/epoxy and carbon/epoxy are used separately and in combination with different patterns of helical and hoop windings, for outer reinforced layers of all composite gas cylinder. Cloud diagram of stress and strain under operating pressure, test pressure and burst pressure are obtained and discussed in detail. The material of the innermost layer of the cylinder i.e. liner should be selected reasonably as it serves as the gas permeation barrier.